The Fungal Microbiome and Asthma - van Tilburg Bernardes, Erik; Gutierrez, Mackenzie W.; Arrieta, Marie-Claire (Frontiers in Cellular and Infection Microbiology, 2020)
Asthma is a group of inflammatory conditions that compromises the airways of a continuously increasing number of people around the globe. Its complex etiology comprises both genetic and environmental aspects, with the intestinal and lung microbiomes emerging as newly implicated factors that can drive and aggravate asthma. Longitudinal infant cohort studies combined with mechanistic studies in animal models have identified microbial signatures causally associated with subsequent asthma risk. The recent inclusion of fungi in human microbiome surveys has revealed that microbiome signatures associated with asthma risk are not limited to bacteria, and that fungi are also implicated in asthma development in susceptible individuals. In this review, we examine the unique properties of human-associated and environmental fungi, which confer them the ability to influence immune development and allergic responses. The important contribution of fungi to asthma development and exacerbations prompts for their inclusion in current and future asthma studies in humans and animal models.